Determinación de magnesio, hierro, manganeso, cobre, zinc y cromo en Unonopsis floribunda (icoja) recolectada en Nina Rumi, Loreto 2021 - Zevallos Fachin, Kenyer Raúl Gabriel (2021)
Essential metals, even in very small amounts, are essential for living beings. Determine the concentration of magnesium, iron, manganese, copper, zinc and chromium in U. floribunda (icoja) collected in Nina Rumi, Loreto 2021. Descriptive research and non-experimental design through sampling by convenience, two kg of root, bark and leaves were obtained; For the analysis, (0.2 g) of each dry pulverized sample was required, which were mineralized and then digested in an acid medium. The analytes were quantified in the atomic absorption spectrophotometer. On average, the trace elements in the five trees showed concentrations that were below 50 mg / Kg, of Cr = Cu <Zn <Mn. Cr showed a tendency in four of the trees to be concentrated in the bark more than in the leaves and was found between 4.3 to 18.92 mg / kg, values slightly higher than those found in medicinal herbs. Magnesium was found in a range of 118.09 to 159.47 mg / Kg. When applying the one-way ANOVA test, it was shown that there is no significant difference between and within groups (? = 0.05) in the content of the metals Mn, Zn, Cu and Mg. The concentration levels correspond to what was expected, with the secondary element Mg being the one found in the highest concentration, followed by Fe, Mn and the other trace elements analyzed.